Zinc Chelation Specifically Inhibits Early Stages of Dengue Virus Replication by Activation of NF-κB and Induction of Antiviral Response in Epithelial Cells - Kar, Meenakshi; Khan, Naseem Ahmed; Panwar, Aleksha; Bais, Sachendra S.; Basak, Soumen; Goel, Renu; Sopory, Shailaja; Medigeshi, Guruprasad R. (Frontiers in Immunology, 2019)
Zinc is an essential micronutrient which regulates diverse physiological functions and has been shown to play a crucial role in viral infections. Zinc has a necessary role in the replication of many viruses, however, antiviral action of zinc has also been demonstrated in in vitro infection models most likely through induction of host antiviral responses. Therefore, depending on the host machinery that the virus employs at different stages of infection, zinc may either facilitate or inhibit virus infection. In this study, we show that zinc plays divergent roles in rotavirus and dengue virus infections in epithelial cells. Dengue virus infection did not perturb the epithelial barrier functions despite the release of virus from the basolateral surface whereas rotavirus infection led to disruption of epithelial junctions. In rotavirus infection, zinc supplementation post-infection did not block barrier disruption suggesting that zinc does not affect rotavirus life-cycle or protects epithelial barriers post-infection suggesting the involvement of cellular pathways in the beneficial effect of zinc supplementation in enteric infections. Zinc depletion by N,N,N’,N’-tetrakis(2-pyridinylmethyl)-1,2-ethanediamine (TPEN) inhibited dengue virus and Japanese encephalitis virus infection but had no effect on rotavirus. Time-of-addition experiments suggested that zinc chelation affected both early and late stages of dengue virus infectious cycle and zinc chelation abrogated dengue virus RNA replication. We show that transient zinc chelation induces ER stress and antiviral response by activating NF-kappa B leading to induction of interferon signaling. These results suggest that modulation of zinc homeostasis during virus infection could be a component of host antiviral response and altering zinc homeostasis may act as a potent antiviral strategy against flaviviruses.